Ubiquitin-related lncRNAs: The new tool for prognosis prediction in prostate cancer - Liu, Xiang; Mei, Wangli; Jin, Liang; Sun, Xianchao; Zhou, Zhen; Xin, Shiyong; Huang, Liqun; Yang, Guosheng; Wang, Jinyou; Ye, Lin (Frontiers in Oncology, 2022)
Objective: To establish ubiquitin-related long noncoding ribonucleic acids (lncRNAs) prognosis prediction model for prostate cancer (Pca). Methods: Data was acquired through the cancer genome atlas (TCGA) database. Ubiquitin-related differentially expressed genes (DEGs) and lncRNAs in Pca were filtered out. UBE2S was selected as representative gene and validated in vitro. Progression free survival (PFS) predictive signature was established with ubiquitin-related lncRNAs screened by Cox regression analyses and internally validated. Nomogram was constructed to assess prognosis of Pca patients. Gene enrichment analysis was performed to explore functional differences based on risk stratification. Between different risk groups, immune status and drug sensitivity were contrasted. Results: 254 ubiquitin-related genes were screened. UBE2S was shown to promote proliferation of Pca cells in vitro. The predictive signature was established based on six ubiquitin-related lncRNAs and validated.The prognosis of Pca patients was worse with increasing risk score. The area under curve (AUC) of signature was higher than of clinicopathological variables (0.806 vs 0.504-0.701). The AUC was 0.811 for 1-year PFS, 0.807 for 3-years PFS and 0.790 for 5-years PFS. The calibration curves of risk score-based nomogram demonstrated high consistency. By contrasting the expression of immune function, cells and checkpoints, we found the signature was closely related to immunity. The high-risk patients were more sensitive to gemcitabine, cisplatin, bortezomib, etc and resistant to bicalutamide. Conclusion: The ubiquitin-related lncRNAs can effectively predict the prognosis of Pca, and may provide new treatment options for Pca.